Asserting and transcending ethnic homophily: How entrepreneurs develop social ties to access resources and opportunities in socially contested environments - Busch, Christian; Mudida, Robert (Strategic entrepreneurship journal, 2024)
Research Summary In socially contested settings, it is often difficult to connect with (diverse) others, and it is unclear how entrepreneurs in these contexts may develop the social ties that previous research has shown to be valuable. We studied this subject matter in Kenya, an ethnically fractionalized society that recently experienced the decentralization of government, which required entrepreneurs to deal with both in‐group and out‐group ethnicities. We conducted an inductive case study of four Nairobi‐based companies and captured the creative tactics that they used to transcend ethnic homophily (by defocusing from ethnicity and reframing the in‐group) while also asserting ethnic homophily (by signaling tribal affiliation and leveraging others' ethnicity). We contribute to a deeper understanding of how and why entrepreneurs in socially contested settings develop social ties. Managerial Summary Entrepreneurs in socially contested settings rely on social networks to access resources and opportunities. However, it is unclear how entrepreneurs in these settings develop and use these networks. We studied this question in an ethnically fractionalized setting that recently experienced the decentralization of government: Kenya. Entrepreneurs who previously provided information technology (IT) services to the central government had to deal with both own‐tribe and other‐tribe contacts to receive new contracts. We studied four Nairobi‐based IT firms that operated across a variety of counties and analyzed the creative tactics that entrepreneurs in this context use to cross ethnic divides while also working with own‐tribe contacts. This contributes to our collective understanding of how and why entrepreneurs in socially contested settings develop diverse social ties to access resources and opportunities.